(untitled) (Journal of Numerical Optimization and Technology Management, 2024)
Warehousing operation is facing huge challenges in meeting tremendous growth of global e-commerce. Conventional ways of handling goods inventory and logistics at warehouse operation are no longer able to cope with phenomenal growth in volume and speed of execution requirement demanded by customers. This research focus on breakthrough transformations of warehouse operation towards Industry Revolution 4.0. The relationship between workforce competency, perceived usefulness and technology innovation factors and warehouse transformations were evaluated. The outcome of this research identified the critical factors and area of improvements which must be considered as the logistic companies embark on transforming warehouse operation towards Industry Revolution 4.0 technologies.